Analisis Reaksi Pasar Atas Pengumuman Stock Split - Paramitha, Dyah (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p10, 2019)
This study reexamines market reaction on stock split announcement. The reexamination was triggered by the increase in the number of investors and occurrence of stock splits recently. The study was conducted in the Indonesia Stock Exchange with the number of samples taken using the non-participant observation method with a purposive sampling technique of 56 companies. Data was collected from the Indonesia Stock Exchange and Yahoo Finance websites. This study uses a 7-day event window. Expected return iscalculated by the market- adjusted model. The analysis technique used is one sample t-test on the cumulative abnormal return. Based on the results of the analysis it is found that there is a positive abnormal return around the announcement of stock split. It shows that stock split has information content. Keywords : Stock split, market reaction, abnormal return.